2019
DOI: 10.1093/pch/pxz134
|View full text |Cite
|
Sign up to set email alerts
|

The screening and management of newborns at risk for low blood glucose

Abstract: Hypoglycemia in the first hours to days after birth remains one of the most common conditions facing practitioners across Canada who care for newborns. Many cases represent normal physiologic transition to extrauterine life, but another group experiences hypoglycemia of longer duration. This statement addresses key issues for providers of neonatal care, including the definition of hypoglycemia, risk factors, screening protocols, blood glucose levels requiring intervention, and managing care for this condition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 70 publications
2
72
0
Order By: Relevance
“…The most commonly reported outcomes focused on the collection and use of colostrum, breastfeeding status and success at various time points, and outcomes related to newborn health and safety. Documentation of the volumes of colostrum that mothers express, and the amount administered to newborns is important to provide insight into the impact of using expressed breastmilk on newborn health versus with standardized newborn hypoglycemia management protocols which can include enteral feeds of breastmilk, breastmilk substitutes, intrabuccal dextrose gel, or intravenous glucose to stabilize newborn blood glucose levels [ 51 ]. Outcomes related to breastfeeding success and status were common among the studies included in this scoping review, however breastfeeding success was often not defined and duration of participant follow-up varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported outcomes focused on the collection and use of colostrum, breastfeeding status and success at various time points, and outcomes related to newborn health and safety. Documentation of the volumes of colostrum that mothers express, and the amount administered to newborns is important to provide insight into the impact of using expressed breastmilk on newborn health versus with standardized newborn hypoglycemia management protocols which can include enteral feeds of breastmilk, breastmilk substitutes, intrabuccal dextrose gel, or intravenous glucose to stabilize newborn blood glucose levels [ 51 ]. Outcomes related to breastfeeding success and status were common among the studies included in this scoping review, however breastfeeding success was often not defined and duration of participant follow-up varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…27 Maternal and infant categories at increased risk for hypoglycemia are listed in Table 2. [47][48][49] Large for gestational age infants born to screened nondiabetic mothers appear not at risk of hypoglycemia 50 nor at increased risk of poor psychomotor development at 4 years of age. 51 Umbilical cord blood glucose does not seem to predict early hypoglycemia.…”
Section: Risk Factors For Hypoglycemiamentioning
confidence: 99%
“…As the ''normal'' range of blood glucose is different for each newborn and depends upon a number of factors 13 including birth weight, gestational age, availability of energy stores, feeding status, and presence or absence of disease, any hypoglycemia management must account for the overall metabolic and physiologic status of the infant, and should not unnecessarily disrupt the mother-infant relationship and breastfeeding. Several authors have suggested algorithms for screening and treatment, 2,47,48,[77][78][79] and the United Nations Children's Fund (UNICEF UK) published a monograph on how to develop a policy on the prevention and management of newborn hypoglycemia. 80 Of the multiple guidelines, algorithms, and practice frameworks available, there are few that are as clear as those from the AAP, 2 the Canadian Paediatric Society, 47 the Swedish National Guideline, 78 and the British Association of Perinatal Medicine 79 as summarized by Dr. Jane Hawdon in 2019 81 (Fig.…”
Section: Dextrose Gel Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Current screening and management guidelines are that neonates with hypoglycemia persisting beyond the first 72 should be investigated further when levels remain ≤2.8 mmol/L, and ≥ 3.3 mmol/L should be the therapeutic glucose target level in symptomatic/at risk infants. Also, before discharge, those experiencing persistent hypoglycemia should have a 5-6 hour fast, while maintaining blood glucose levels ≥3.3 mmol/L, to ensure safety at home [39].…”
Section: Predisposing Factors For Brain Injurymentioning
confidence: 99%